ANALISIS PERBANDINGAN KINERJA REKSA DANA SAHAM KONVENSIONAL PENDEKATAN METODE SHARPE DAN TREYNOR MEASUREMENT - Zastya Esfarenza; Sulastri Sulastri; Husni Thamrin (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2018)
The aim of the study is to know the difference between the measurement of the performance of Conventional equity funds using Sharpe and Treynor Methods. The population of the study was a conventional equity funds listed in the Financial Services Authority for the year 2013-2016. The number of samples in this study were 32 conventional stock mutual funds by using purposive sampling. This study also used data Composite Stock Price Index (CSPI), the net asset value of connventional equity funds and the interest rate of Bank Indonesia Certificates (SBI) were taken on a monthly basis. This analysis technique using the Mann-Whitney test. The results showed a conventional equity fund performance as measured by the method Sharpe dan Treynor method showed better results than the market performance (JCI) and there is a difference between performance measurement using a conventional equity fund Sharpe and Treynor.